Co-creating a simulation with students as active partners: a social work experience - Huseinovic, Dennis; Yaschuk, Eli; Dube, Kealey; dos Santos Nogueira de Góes, Fernanda; Rohatyn-Martin, Natalia K.; Fidelak, Deanna (My University, 2025)
This case study presents a students-as-partners (SaP) approach to field education in social work. In particular, it describes the co-creation of a simulation-based learning experience co created and delivered by faculty, staff and two students—a student who experiences disability-related barriers and a theatre student. It explores the principles inherent in a student as partners philosophy as well as a universal design approach were used to co-create the simulation scenarios. The study examines the application of a student as partners approach and universal design for learning (UDL) principles in the development of simulation scenarios, both of which emphasize inclusivity, collaboration, and engagement. The case study also highlights how a collaborative, inclusive approach to simulation-based learning enhances student engagement and learning outcomes, particularly for students experiencing barriers. The experience demonstrates the value of interdisciplinary partnerships and offers insights for supporting students with disabilities in social work education, suggesting future directions for the integration of SaP and UDL in academic settings.
Keywords: student as partners; social work; co-creation; simulation-based learning; disability-related barriers